Free solvent oxidation of molecular benzyl alcohol by newly synthesized AuPd/titania catalysts - Mohd JamJam, Norasidah; Yun Hin, Taufiq Yap; Muhamad, Ernee Noryana; Saiman, Mohd Izham; Saleh, Tawfik A. (Elsevier BV, 2019)
Oxidation of benzyl alcohol is one of the industrial reactions utilized to produce chlorine-free benzaldehyde. Interestingly, supported gold nanoparticle catalysts are efficient towards the oxidation reaction of alcohol without involving any solvents, hence following the terms of green technology. In this study, nanoparticles of bimetallic gold palladium supported on TiO2 were synthesized using the sol-immobilization method. The catalysts were structurally characterized using X-ray Diffraction (XRD), Transition Electron Microscopy (TEM), and Brunauer Emmett Teller (BET) instruments to get insight into the synergistic effect between both Au and Pd. The catalytic activities of the prepared catalysts were evaluated towards the oxidation of benzyl alcohol over tert-butyl hydroperoxide (TBHP). The results obtained from the catalytic evaluation of the prepared catalysts indicated that 0.5 wt% Au-0.5 wt% Pd/TiO2 is the best catalyst among other ratios with a 3.1 ± 0.8 nm particle size and the TEM results reveal the consistency value of a particle for each Ausingle bondPd ratio. The prepared catalyst consists of 0.50 wt% Au and 0.50 wt% Pd/TiO2 which exhibited remarkably enhanced catalytic activity (>19%) and selectivity of benzaldehyde (∼80%) when compared to another metal loading of the Ausingle bondPd catalyst. The reusability of the prepared catalyst was evaluated more than five times, and the results indicated minimal loss in activity where a low concentration of gold was leached (0.05 mg/L) under optimal reaction conditions.